UPAYA WORLD VISION MELAKUKAN PELESTARIAN HUTAN MELALUI SEKOLAH HIJAU DI KABUPATEN SAMBAS, KALIMANTAN BARAT TAHUN 2011-2014 - Pangaribuan, Edwin Peter Mathews; Priadarsini, Ni Wayan Rainy; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2016)
ABSTRACT Environmental issue such as deforestation is one of serious threats toward national development. Especially for Indonesia as developing country. Society does not have power to fight the palm oil exploitation in Sambas District, West Kalimantan. Awareness-Raising as empowerment so that people have power against deforestation issue in Sambas. Advocacy helps people to gain their rights back on environment-based education against deforestation through forest conservation learning at school. The effort is a political act to influence people and government. The efforts as a bottom-up approach through the green schools in Sambas. This research aims to describe the effort undertaken by World Vision as INGO helped forests conservation in Sambas, West Kalimantan. Key words: World Vision, empowerment, Bottom-up Approach